PEMANFAATAN PLATFORM DIGITAL DALAM PEMBELAJARAN ONLINE SELAMA MASA PANDEMI COVID-19 DI SEKOLAH DASAR - Dera Sulastri; Luthfi Hamdani Maula; Din Azwar Uswatun (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
This study aims to describe the use of digital platforms in the online-based learning process during the covid-19 pandemic in elementary schools. This research uses descriptive qualitative method carried out with a qualitative approach. The object of this study was elementary school teachers in SDN Tanjungsari. Data source technique is using purposive sampling technique. When the research was conducted in the even semester of the 2019/2020 school year. Data collection techniques used are through in-depth interviews conducted directly by telephone. Technical analysis of data using descriptive technical analysis. The results showed that the dominant digital platform used in the asynchronous or indirect online learning process at SDN Tanjungsari was the whatsapp social media platform by utilizing the existing features. Besides whatsapp, the zoom cloud meetings platform is also used in the online learning process in a direct or synchronous. Overall the teaching and learning process online through whatsapp and zoom cloud meetings can be implemented well.